Special aspects of guardingand protecting sports facilities (Belügyi Szemle, 2024)
Aim: The arrangement and organisation of sports events is a coordinated activity involving several organisations. The purpose of the research is to examine and reveal the special guarding and protection requirements of sports facilities and sports event venues.Methodology: After collecting and processing the reference literature, the Authors applied a qualitative method and focused on the methods and means of providing sports facilities, and looked for specifics from their own point of view. During the research, they used both empirical and logical methods. In order for the earned knowledge to contribute to the solution of practical problems, they chose the activity of practice-oriented research.Findings: Starting from the 1960s, and mainly from the 1980s, the arrangement and organisation of sports events is not just a professional sports issue. The capital injected by economic actors was aimed at organising family, cultural and entertainment events. As a result, unlike before, the sports facilities initially became multi-functional, and then the modern facilities became multi-functional venues. Due to its multi-functionality, special requirements for the security and protection of the venues and the facilities created in their surroundings, with different sports and economic purposes, have developed.Value: The basis of the security technology of sports facilities and the commercial, economic, entertainment, cultural and service units located in them is the security of objects, as well as personal and property security. Guarding and protecting the proper operation of the facilities is an organised and coordinated activity in the same way as in the case of sports events held in the facilities, but the method of implementation is not the same.